2018
DOI: 10.1111/imig.12539
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Capital of Recruitment Decision‐Makers and its Influence on their Perception of Person‐Organisation Fit of Skilled Migrants

Abstract: This article examines how recruitment decision‐makers’ cultural capital can influence their concerns about the organizational fit of skilled migrants (SM). We used survey data and interviews with Information Technology organizations in Australia. The study highlights the decision‐makers’ relatively poor understanding of non‐western cultures and how it negatively influences their perception of candidates from non‐western backgrounds. Furthermore, this study also notes how organisational cultural values and deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…When current research points to involuntary bias and organizational limitations in the recruitment of skilled migrants (e.g. Almeida et al, 2019;Crowley-Henry and Al Ariss, 2018;Ghumman and Ryan, 2013;Ogbonna and Harris, 2006), we show that this normality is much more than a simple state of affairs to which the candidate is expected to fit. Rather, it is a valued norm that leads to the reproduction of structural discrimination.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…When current research points to involuntary bias and organizational limitations in the recruitment of skilled migrants (e.g. Almeida et al, 2019;Crowley-Henry and Al Ariss, 2018;Ghumman and Ryan, 2013;Ogbonna and Harris, 2006), we show that this normality is much more than a simple state of affairs to which the candidate is expected to fit. Rather, it is a valued norm that leads to the reproduction of structural discrimination.…”
Section: Introductionmentioning
confidence: 65%
“…Studies such as that of Holgersson et al (2016) stress that job applicants with a migrant background are rarely considered potential candidates for high-status positions. Many studies suggest that the human capital of skilled migrants (their education, training and accumulated professional experience) is perceived as different and poorer compared to that of local candidates (see Crowley-Henry and Al Ariss, 2018) and is therefore devalued (Almeida et al, 2019;Zikic, 2015). When migrants are recognized as potential candidates, then, they may not face an equal chance of success.…”
Section: The Role Of Organizations In (Co-)constructing Migrant Emplomentioning
confidence: 99%
See 2 more Smart Citations
“…They found that organizational characteristics such as organizational type, client ethnicity and management style have an impact on the employers' level of tolerance, comfort levels and stereotypes in relation to SMs, job specifications' design, competency frameworks and selection methods, all of which can subsequently result in either the selection or rejection of SMs in the hiring process. Almeida, Waxin & Paradies (2018) found that recruiters with lower levels of cultural capital (i.e. knowledge and experience about diverse cultures) were less likely to think that SMs with different communication styles, international education and experiences, and appearances (attire and religious affiliation) would fit in their company.…”
Section: At the Meso-organizational Levelmentioning
confidence: 97%